Platelet-Rich Fibrin Promotes Osteoblast Recruitment-Associated Periodontal Regeneration via Macrophage Polarization - Hudi Xu; Huan Jing; Richard J. Miron; Yulan Wang; Dagang Xu; Xiaoxin Zhang (Stem Cells International)
Conclusion: The present study explored a promising mechanism of the periodontal regeneration function of PRF, by inducing macrophage polarization, thereby enhancing osteoblast recruitment, with horizontal centrifugation significantly improving these findings.